2008
DOI: 10.1021/la703152q
|View full text |Cite
|
Sign up to set email alerts
|

Friction Dynamics of Confined Weakly Adhering Boundary Layers

Abstract: The nanotribological behavior of self-assembled monolayers is investigated. The latter accommodate friction through transient relaxation and dilatancy effects whose kinetics depends on the structure of the confined layers. Thus, the molecular ordering onto the surfaces controls the level and the stability of the friction coefficient. Moreover, the behavior of these systems is theoretically accounted for using a model based on the kinetics of formation and rupture of adhesive bonds between the two shearing surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…SFA has confirmed that saturated alkyl chain OFMs adsorb from solution to form vertically oriented monolayers on mica [59,61] and also cobalt surfaces [58,60] while QCM has shown that oleic acid molecules appear to adsorb parallel to the surface on iron [66]. In AFM/LFM a sphere or sharp tip is rubbed against a substrate to provide a reasonably close analogue of a high pressure sliding asperity contact.…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…SFA has confirmed that saturated alkyl chain OFMs adsorb from solution to form vertically oriented monolayers on mica [59,61] and also cobalt surfaces [58,60] while QCM has shown that oleic acid molecules appear to adsorb parallel to the surface on iron [66]. In AFM/LFM a sphere or sharp tip is rubbed against a substrate to provide a reasonably close analogue of a high pressure sliding asperity contact.…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…These include the surface forces apparatus (SFA) [58][59][60][61], atomic/lateral force microscope (AFM/LFM) [62][63][64][65], quartz crystal microbalance (QCM) [66], ultrathin film interferometry (UTFI) [67], neutron reflectometry [68,69] and various surface-specific vibrational spectroscopies [70][71][72]. Methods were also developed to generate model close-packed monolayers by chemical grafting of self-assembled alkylthiols and alkyl siloxanes on solid surfaces [73][74].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…Eventually, at very high speeds Drummond et al suggested that all nano-junctions were broken and friction originated from thin film viscous shear. Mazuyer et al have recently applied Drummond's model to the measured friction behaviour of solutions of two organic friction modifiers in polyalphaolefin base fluid in a surface forces apparatus [89].…”
Section: Boundary Frictionmentioning
confidence: 99%
“…In addition to Schallamach's (and Eyring and Prandtl's) principle, that applied force reduces the energy barrier, thus allowing more rapid junction breaking, Drummond et al also assumed that all junctions will break when they reached a critical elastic deformation. Mazuyer et al have recently applied Drummond's model to the measured friction behaviour of solutions of two organic friction modifiers in polyalphaolefin base fluid in a surface force apparatus [25].…”
Section: Schallamach Modelmentioning
confidence: 99%